RESPONSE OF GREEN BEAN TO NITROGEN FIXING BACTERIAL INOCULATION AND MOLYBDENUM - & Al-Jebory, Al-Rukabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The experiment was conducted at the fields of the Department of Horticulture and Landscape Gardening, College of Agriculture, University of Baghdad, Aljadrya campus during the spring season of 2015 to study the response of green beans to the inoculation with nitrogen fixing bacteria including Rhizobium phaseoli, Azotobacter chroococcum, and Azospirillum brasilense and molybdenum. The experiment was carried out according to the randomized complete block design (RCBD) with three replications each included 11 treatments represent the interactions between nitrogen fixing bacteria strains, molybdenum solo application, molybdenum and bacteria strains interactions, in addition to the recommended nitrogen application and control treatment. Results were analyzed using the least significant differences (LSD) test at 5% level of significance. Results showed that treatment with all three bacteria strains and Mo (T11) gave the most significant value of leaf area and N, P, Fe, Mo in the pods which gave 59.50 dm2.plant-1, 2.24%, 0.25%, 51.67 mg.kg-1, and 0.34 mg.kg-1, respectively. However, treatment with nitrogen (T2) significantly increase potassium percentage in plant pods, root branching, and leaf chlorophyll content that reached 1.71%, 12.11 branch.plant-1, and 147.98 mg.100 g-1 fresh weight. Moreover, treatment with both R. phaseoli and A. chroococcum (T5) gave the highest root dry weight of 7.78 g.plant-1 while the treatment with both R. phaseoli and A. chroococcum and Mo (T9) gave the highest root nodular fresh weight of 633.51 mg.plant-1. Treatments with R. phaseoli alone (T4) and with both R. phaseoli and A. chroococcum (T5) significantly increased shoot number that reached 4.11 shoot.plant-1 while treatment with all bacteria strains (T7) yielded the highest pod’s weight of 5.91 g. As for the total yield, treatment with both R. phaseoli and A. chroococcum and Mo showed to significantly increase total production that gave 20.96 Ton.Ha-1.